ROOM RENTAL IN SYSTEM DESIGN IN XYZ - Ismail Ismail; Ir. Don Elsyafitra (Jurnal Sistem Informasi, 1998)
In this system, room rentals, tenants receive a blank rental rooms provided in conjunction with a room key, when the tenant signed up. Supervision of a leader is absolutely necessary to the smooth and avoid the deviations that may occur in activities or daily work.